Chemical composition and biological activities of Jamaican Cannabis sativa essential oils as the plant matures. (19th February 2023) - Clarke, Kellyann; Porter, Roy; Facey, Petrea; Thoms‐Rodriguez, Camille
Abstract: Cannabis sativa is a flowering plant belonging to the Cannabinaceae family. There have been numerous ongoing studies globally on C. sativa which include investigating the yield and quality of essential oils. However, this study is the first to assess the chemical composition and biological activities of Jamaican C. sativa essential oils (EOs) extracted via hydrodistillation as the plants mature from week 8 through to week 12. EOs from fresh landrace female plants were analysed by gas chromatography–mass spectrometry (GC–MS) and GC coupled to a flame ionization detector (GC‐FID). Cannabis sativa essential oils were screened for their in vitro antimicrobial activity using the disc diffusion method and further with tube dilution method. The antioxidant properties were investigated using the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assay. In total, 36 constituents were identified in the C. sativa EOs by comparison of the Kováts retention indices (RI), the mass spectra data with those in the Natural Institute of Standards and Technology (NIST) library and by co‐elution with authentic samples where available. The major constituents were β‐caryophyllene (25.34%) and α‐humulene (α‐caryophyllene) (10.94%) both at the highest levels in week nine and were the most abundant constituents present at all stages of maturity. All extracted C. sativa essential oils did not exhibit antioxidant properties. However, the C. sativa essential oils exhibit significant to moderate antimicrobial property against the test gram‐positive microorganisms, Enterococcus faecalis, Streptococcus Group A and Streptococcus Group B with MIC values ranging from 16 to 125 μg/mL. Abstract : Jamaican Cannabis sativa essential oils extracted via hydrodistillation as the plants mature from week 8 through to week 12 were assessed for its chemical composition and biological activities. A total of 36 compounds were identified with the major constituents being β‐caryophyllene (25.34%) and α‐humulene (10.94%) both at highest level in week nine and were the most abundant constituents present at all stages of maturity. The oils showed antimicrobial against three gram‐positive micro‐organisms assayed, however no significant antioxidant activities were observed.